2015
DOI: 10.1002/jhm.2344
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to access an in‐hospital supervised injection facility among hospitalized people who use illicit drugs

Abstract: Background Despite the reliance on abstinence-based drug policies within hospital settings, illicit drug use is common among hospitalized patients with severe drug addiction. Hospitalized people who use illicit drugs (PWUD) have been known to resort to high-risk behaviours to conceal their drug use from healthcare providers. Novel interventions with potential to reduce high-risk behaviours among PWUD in hospital settings have not been well studied. Objective The objective of the study was to examine factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
3
20
0
Order By: Relevance
“…Our study also found that people who use non-injection crack cocaine daily were more likely to report willingness to use an in-hospital SIR. This is consistent with previous studies documenting associations between high-intensity drug use and willingness to use in-hospital supervised injection facilities [32]. Our finding of an association between daily crack use and willingness to use an in-hospital SIR is encouraging given that high-intensity use of crack cocaine has previously been linked to various high-risk sexual and drug use behaviours and harms [10] and that a key objective of supervised consumption facilities is to attract higher-risk PWUD [30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study also found that people who use non-injection crack cocaine daily were more likely to report willingness to use an in-hospital SIR. This is consistent with previous studies documenting associations between high-intensity drug use and willingness to use in-hospital supervised injection facilities [32]. Our finding of an association between daily crack use and willingness to use an in-hospital SIR is encouraging given that high-intensity use of crack cocaine has previously been linked to various high-risk sexual and drug use behaviours and harms [10] and that a key objective of supervised consumption facilities is to attract higher-risk PWUD [30].…”
Section: Discussionsupporting
confidence: 93%
“…The tendency for SIR-willing people who smoke crack cocaine to have ever used drugs in hospital is largely consistent with a previous study demonstrating that having a history of in-hospital drug use was positively associated with willingness to use an in-hospital supervised injection facility among people who inject drugs [32]. This finding likely reflects an appreciation for in-hospital SIRs based on prior difficult hospitalisation experiences [15,17], particularly given that the primary reasons cited for willingness to use an in-hospital SIR were based on the desire to remain in hospital and circumvent structural pressures that promote risky drug use practices and premature discharges.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Covid-19 has focused a light on the counter-productivity of this mentality and highlighted the need for and feasibility of change. In-hospital overdose prevention or supervised injection facilities are available to patients in several hospitals in Canada and must be made available in the United States ( Dong, Brouwer, Johnston, & Hyshka, 2020 ; Ti et al, 2015 ). In response to Covid-19, the British Columbia Ministry of Health recommended additional harm reduction approaches.…”
mentioning
confidence: 99%
“…The risk of fatal overdose in these settings may be modifiable through more timely provision of opioid substitution therapies and/or naloxone, safer injecting spaces (which have been proposed in Canada 23 ), or improved protocols for management of people who are dependent on opioids. A study of hospital opioid substitution protocols is currently underway, led by Release and LSHTM, with early findings showing wide variation in protocols.…”
Section: Introductionmentioning
confidence: 99%